Pathophysiological roles of integrins in gliomas from the perspective of glioma stem cells - Wang, Maoyu; Shen, Sen; Hou, Feng; Yan, Yaohua (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma is the most common primary intracranial tumour and is also one of the most malignant central nervous system tumours. Its characteristics, such as high malignancy, abundant tumour vasculature, drug resistance, and recurrence-prone nature, cause great suffering to glioma patients. Furthermore, glioma stem cells are the primordial cells of the glioma and play a central role in the development of glioma. Integrins—heterodimers composed of noncovalently bound α and β subunits—are highly expressed in glioma stem cells and play an essential role in the self-renewal, differentiation, high drug resistance, and chemo-radiotherapy resistance of glioma stem cells through cell adhesion and signalling. However, there are various types of integrins, and their mechanisms of function on glioma stem cells are complex. Therefore, this paper reviews the feasibility of treating gliomas by targeting integrins on glioma stem cells.